All-Round Training In Higher Education: Content Analysis of Political Speeches (2017)
The present article of research shows part of the results of a work which inquired into the all-round training in higher education. Its purpose is to present the analytical approach to supranational and national documents that guide the professional training. This analysis was carried out in the basis of 20th and 21th-century theoreticians who conceptualized the allround training and the higher education mission. The all-round training is understood as an educational model focused on the development of human dimensions which should be addressed by higher education. The method used was the content analysis, a tool that allows identifying tendencies within the paragraphs and the words of the documents. A political speech oriented towards personal growth of people as social and individual beings that correspond to the all-round training definitions was found. Despite the interest awakened by humane education, institutions aim their interests to economic development whilst forgetting their role as social educator in order to achieve a just and peaceful society.